+0  
 
0
30
2
avatar

how do you simplify 5 - (2x + 3)

Guest Sep 12, 2017
Sort: 

2+0 Answers

 #1
avatar
0

5-2x -3 

2x=5+3

2x=8

x=8:2 

x=4

Guest Sep 12, 2017
 #2
avatar+76168 
+1

 5 - (2x + 3)  =

 

5 - 2x  - 3   =

 

2 - 2x

 

 

cool cool cool

CPhill  Sep 12, 2017

21 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details